Effect of Screw Length and Geometry on Interfragmentary Compression in a Simulated Proximal Pole Scaphoid Fracture Model. (May 2020) - Patel, Samik; Giugale, Juan M.; Debski, Richard E.; Fowler, John R.
Background: The objective of this study was to determine interfragmentary compression forces based on screw length and geometry for simulated proximal scaphoid fractures.Methods: Sixty-four foam model simulated fractures were stabilized with screws of various length (10 mm, 18 mm, 20 mm, or 24 mm) and geometry (central threadless or fully threaded) across a proximal fracture. Interfragmentary compression was measured at the simulated fracture site upon fixation. An independent sample t test and 1-way analysis of variance were performed to assess differences in interfragmentary compression.Results: Fixation utilizing a 10-mm screw generated significantly less interfragmentary compression than fixation utilizing a 20-mm or 24-mm screw. When accounting for both screw length and geometry, an 18-mm central threadless screw generated greater interfragmentary compression than a 20-mm and 24-mm fully threaded screw; there was no significant difference in compression between an 18-mm and 24-mm central threadless screw.Conclusions: The design of headless compression screws allows for maximal interfragmentary compression at the screw midpoint; we questioned whether a short screw centered on the fracture site resulted in superior compression to a longer, noncentered screw. Our data suggest that centering a small screw (10 mm) along a proximal fracture generates significantly less interfragmentary compression than a longer, noncentered screw. Our results demonstrate that balance between maximizing screw length and centering the screw on the fracture is vital toward maximizing interfragmentary compression for the fixation of proximal third scaphoid fractures.